2021
DOI: 10.1007/s10764-021-00261-z
|View full text |Cite
|
Sign up to set email alerts
|

A 24-Year Record of Female Reproductive Dynamics in Two Sympatric Mouse Lemur Species in Northwestern Madagascar

Abstract: Seasonal reproduction is widespread among primates but the degree of reproductive synchrony and plasticity can vary, even between closely related species. This study compares the dynamics of female reproductive seasonality in two mouse lemur species, Microcebus murinus and M. ravelobensis, in Ankarafantsika National Park, Madagascar, across 24 years. We collected 4321 records of female reproductive state from 1033 individual females (319 M. murinus, 714 M. ravelobensis). The analyses revealed disparate reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Similarly, the present study finds evidence that effective prezygotic mechanisms of reproductive isolation are largely in place for M. murinus and the more distantly related M. ravelobensis, though results also demonstrate that interspecific mating between mouse lemur species must occur occasionally, leading to the production of fertile offspring. The rarity of such events is not surprising, as it has already been shown that both species differ in habitat preferences [49,71,72], reproductive schedules [73][74][75], and advertisement calls [76], and can discriminate conspecifics based on olfactory signals [77,78]. Further studies are needed to clarify whether M. murinus also hybridizes with its congeners M. berthae, M. myoxinus and M. bongolavensis at other localities in order to identify under which circumstances reproductive isolation breaks down in mouse lemurs.…”
Section: Occasional Hybridization Between M Murinus and M Ravelobensismentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the present study finds evidence that effective prezygotic mechanisms of reproductive isolation are largely in place for M. murinus and the more distantly related M. ravelobensis, though results also demonstrate that interspecific mating between mouse lemur species must occur occasionally, leading to the production of fertile offspring. The rarity of such events is not surprising, as it has already been shown that both species differ in habitat preferences [49,71,72], reproductive schedules [73][74][75], and advertisement calls [76], and can discriminate conspecifics based on olfactory signals [77,78]. Further studies are needed to clarify whether M. murinus also hybridizes with its congeners M. berthae, M. myoxinus and M. bongolavensis at other localities in order to identify under which circumstances reproductive isolation breaks down in mouse lemurs.…”
Section: Occasional Hybridization Between M Murinus and M Ravelobensismentioning
confidence: 99%
“…In addition, only M. murinus males (n = 7) were captured at this location during our field season in 2017, suggesting that these microhabitats may not to be favorable for female M. murinus. The temporarily limited availability of conspecific mates during some years and in some places, possibility aggravated by the very short mating season and brief receptive periods characteristic of female mouse lemurs [73,74], may thus lead to accidental hybridization. Given ongoing habitat loss and fragmentation in western Madagascar, such scenarios may become more likely in the future and should add to existing conservation concerns.…”
Section: Under Which Circumstances May Hybridization Occur?mentioning
confidence: 99%
“…As M. murinus was not found in JBB across all years and months, the variable combining sampling site and host species was necessary to avoid modeling errors. Juvenile age was deduced from a low initial body mass (clearly below average) and its steady increase over the first months of capture (Radespiel et al, 2021). To control for pseudoreplication based on multiple sampling of single hosts, host identity ("animal ID") was added as a random factor.…”
Section: Discussionmentioning
confidence: 99%
“…M. murinus and M. ravelobensis live in partial sympatry (i.e., occurring together in some forests but alone in others) in the two study sites, exhibit similar body sizes (ca. 60 g), overlapping diets and seasonal reproductive activity (Radespiel et al, 2021; Thorén et al, 2011; Zimmermann et al, 1998). According to previous studies (Kiene et al, 2020; Klein et al, 2018), seasonality, habitat fragmentation, host sex, body mass, and species seem to be important determinants of host ectoparasite infestations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation